ANALYSIS OF DIFFERENT LEVEL OF RESILIENCE IN FARMING COMMUNITIES IN FLOOD DISASTER-PROPOSED AREA AT BOJONEGORO REGENCY - Widodo, Bambang Sigit; Khusna, Nur Isroatul; Silviariza, Waode Yunia (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2021)
Abstract: This study aims to determine the level of resilience in farming communities in flood-prone areas which include Bojonegoro District, Balen District, and Trucuk District. This type of research is quantitative using a survey approach. The sample in this study amounted to 153 respondents with predetermined criteria, namely farmers with land ownership of less than 1 hectare. Collecting data using a resilience instrument developed by CD-RISC, and then modified by the researcher according to the characteristics of the respondents. Data analysis used one way ANOVA test. The results showed a p value < 0.001, so there was a significant difference between the levels of resilience in the three regions with the highest value in the Bojonegoro sub-district, namely 112.805, which means that it has a better resilience level than Balen and Trucuk Districts. The frequency in which the Bojonegoro sub-district receives floods > 2 times a year makes the people in this area have the ability to adapt, so that their resilience is better. Keywords: resilience, farmers, flood disaster